Some problems of health care workers’ civil liability for medical malpractice - Prudnikova, M.Yu. (KSU publ., 2019)
The article covers the problems of civil liability in medicine. The relevance is caused by medical disputes resonance concerning medical malpractice when rendering health care services and the difficulty of their legal treatment. The author believes that a lack of clear criteria for medical error leads to gaps in the law enforcement practice. The author points out the need to improve legislation on physicians’ responsibility concerning conceptual questions, and also offers the definition of legal categories that exclude health care workers’ liability. The article analyzes the scientific and practical approaches to determining the medical and legal malpractice, its nature is studied and features are defined. It is noted that a medical error in all cases should be considered as the grounds for civil liability. A medical error is considered in relation to the concepts of «accident in medicine», as well as the category of «objective omission» proposed by the author, which, in accordance with his judgment, must have different legal consequences. Particular attention is paid to the evidence of reasonable medical risk as the basis for the release of medical workers from liability. The results of the study are novel and original, the author’s position is justified and of interest to employees whose activities are related to the interpretation and application of the rules on the responsibility of medical workers.
Keywords: health services; liability; malpractice; reasonable medical risk; accident in medicine; patient; health care; medical worker